Tinjauan Yuridis Regulasi Investasi Asing Dalam Penyelenggara Layanan Pinjam Meminjam Uang Berbasis Teknologi Informasi (Peer to Peer Lending) Konvensional Dan Syariah Di Indonesia - Harlie Subekti; Bukhori Muslim Muslim; Faris Satria alam (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
The purpose of this study is to examine regulations relating to foreign investment in the Financial Services Authority Regulation Number 77 of 2016 about Information Technology-Based Borrowing-Lending Services, which was published in 2016. It is burdensome if it is applied in a systematic manner in conjunction with other laws and regulations. Apart from that, the implementation of the organizers in accordance with the Financial Services Authority Regulation Number 77 of 2016 and market behavior (ethical behavior) governed by the organization, in this case the Indonesian Joint Funding Fintech Association, are equally important (AFPI). In this study, the research method is based on a statutory methodology. The type of research used in this study is normative empirical research, with data collection methods such as library research and interviews serving as the primary data sources. According to the findings of the study, foreign investment in the Financial Services Authority Regulation is in conflict with the aforementioned regulations, and the implementation for the operator is classified as less than optimal due to the limited authority of the Financial Services Authority, which is only classified as an authority regulation and not a law, and the implementation for the operator is classified as less than optimal.